Hemiscrotal agenesis: Pathogenesis and management strategies. (14th March 2016) - Nishio, Hidenori; Mizuno, Kentaro; Moritoki, Yoshinobu; Kamisawa, Hideyuki; Naiki, Taku; Kurokawa, Satoshi; Nakane, Akihiro; Okada, Atsushi; Yasui, Takahiro; Hayashi, Yutaro
Abstract: Hemiscrotal agenesis is among the rarest anomalies in scrotal development disorders. As it has only been reported in three cases, the clinical manifestations remain unclear. We report a case of hemiscrotal agenesis with ipsilateral cryptorchidism. Based on the thermal assessment of the scrotum, concurrent scrotoplasty and orchiopexy were carried out, and the scrotoplasty improved the thermal environment of the fixed left testis. Furthermore, the low expression of androgen receptor and steroid‐5‐alpha‐reductase, alpha polypeptide 2 in the affected side of the scrotum likely resulted in the characteristics of absent scrotal rugae, and pigmentation on histological and biological analyses. For future fertility, we believe that scrotoplasty should be considered as a management option for hemiscrotal agenesis.